Computational and experimental investigation of biogenic zinc oxide nanoparticles synthesized from Clausena dentata leaf extract for α-amylase inhibition and K562 leukemia cell therapy - Vijayalakshmi, Kakkan; Vidhyulatha, Nagappan; Aldawood, Saad; Manjulabai, Appunrao; Aboorva, Mathivanan; Manjula, Ramamoorthy; Velmurugan, Gunasekaran; Nagaraj, Karuppiah (Food bioscience, 2025)
This study presents a novel green synthesis of zinc oxide nanoparticles (ZnO NPs) using Clausena dentata leaf extract as a biogenic reducing and stabilizing agent, offering an eco-friendly alternative to conventional chemical methods. Unlike previous approaches, this work integrates the phytochemical potential of Clausena dentata with ZnO NPs to enhance their biomedical applications. Zinc oxide nanoparticles (ZnO NPs) were synthesized using Clausena dentata leaf extract as a green reducing and stabilizing agent. The synthesis was achieved by reacting the leaf extract with a zinc nitrate precursor under controlled conditions, followed by calcination at 400 °C. Comprehensive characterization using UV-vis spectroscopy, FTIR, XRD, SEM, and EDX confirmed the nanoscale size, hexagonal crystal structure, and biogenic origin of the ZnO NPs. The micrograph reveals the presence of nanorods alongside cubic and hexagonal formations, with x-ray diffraction analysis confirming a crystallite size of approximately 14 nm for ZnO NPs. The biomedical potential of ZnO NPs was evaluated through in vitro antidiabetic and antitumor assays. The α-amylase inhibition assay revealed significant antidiabetic activity, demonstrating enzyme inhibition at varying nanoparticle concentrations. The IC50 value for ZnO NPs was determined to be 43.09 μg/mL for α-amylase inhibition, indicating notable, though lower, efficacy compared to metformin. Additionally, ZnO NPs exhibited anticancer activity against the K562 cell line, with an IC50 value of 38.36 μg/mL, demonstrating a dose-dependent suppression of cell viability. These findings highlight the potential of ZnO NPs for biomedical applications, particularly in enzyme inhibition and cancer therapy. Molecular docking studies supported the experimental findings, showing strong interactions between ZnO NPs and target proteins, with binding energies of −4.7 kcal/mol for α-amylase (PDB ID: 2QV4) and −4.5 kcal/mol for a cancer-associated protein (PDB ID: 2HYY).
Online verfügbar: 15. März 2025, Artikelversion: 20. März 2025
Gesehen am 01.10.2025